A Fuzzy Soft Set Theoretic Approach in Decision Making of Covid-19 Risk in Different Regions - Awasthi, Anurag; Srivastava, Sudhir Kumar (Communications in Mathematics and Applications, 2021)
In the present paper, we apply the theory of fuzzy soft sets to solve a decision making problem related to Covid-19. We give an example which shows that the method can be successfully applied to the burning problem of Covid-19 that contains uncertainties and find result regarding to the risk of Covid-19 in particular region.
Keywords: Soft set; Fuzzy soft set; Weighted fuzzy soft matrix; Decision making; Covid-19